Fiscal policy transformation under economic crisis - Lihong, Zhu (Herald of Economics, 2025)
Introduction. The worldwide economic crisis can exert significant and extensive impacts on a nation’s economy. Whether instigated by financial downturns, recessions, or international disturbances (such as the COVID-19 pandemic), these crises can disrupt the established economic framework and present considerable obstacles. The repercussions of a global economic crisis on a nation’s economy may be observed across multiple domains, influencing diverse economic indicators, sectors, and the overall social structure. The effects of a global economic crisis on a nation’s economy are complex and can manifest in both immediate and enduring ways. In the short term, such crises often lead to economic downturns, increased unemployment rates, financial turmoil, and heightened social unrest. Over the long term, the repercussions may involve alterations in the economic framework, difficulties in managing public debt, and shifts in governmental priorities. The extent and duration of the crisis’s impact will significantly depend on the state’s fiscal and monetary strategies, as well as its capacity to implement coordinated recovery initiatives. It is essential for governments to comprehend these dynamics in order to formulate effective strategies, promote economic recovery, and enhance resilience against future economic disruptions.Research Objective. The aim of the study is the systematic study and analysis of fiscal policy in the conditions of the global economic crisis and development of recommendations for the formation of an anti-crisis strategy and the principles of its effective transformation. Methods. The study employs economic-statistical analysis to examine the fiscal policy instruments using under global economic crisis. Additionally, general scientific and empirical approaches, as well as tools from the field of economic science, are utilized. Methods such as synthesis, comparison, aggregation, and grouping are also applied to enhance the comprehensiveness of the research.Results. The study has researched the decline in revenue collection across both advanced economies and emerging markets and developing economies. It is proposed the key principles for policymakers when developing their strategies and recommended ways that can assist nations in formulating an effective strategy to address various adverse shock.Perspectives for further research on fiscal policy in the context of global crises is extensive and significantly pertinent, especially as the world encounters a growing array of intricate and interrelated economic difficulties. Scholars, policymakers, and various institutions are deeply invested in exploring how fiscal strategies can be optimized to alleviate crises, facilitate recovery, and enhance long-term economic stability.